THE ART OF SUSTAINABLE URBANIZATION: INSIGHTS FROM RERA'S IMPACT ON INDIA'S REAL ESTATE LANDSCAPE - Prashar, Rekee; Tomer, Aditya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Real Estate (Regulation and Development) Act (RERA), enacted in 2016, has been a pivotal force in transforming the Indian real estate sector by enhancing transparency, accountability, and efficiency. This paper examines the interplay between regulatory frameworks and the visual and cultural dynamics of sustainable urbanization. Through an extensive review of existing literature, policy analysis, and case studies, the research investigates the multifaceted impact of RERA on various stakeholders, including developers, buyers, and regulatory bodies. RERA's stringent regulations have instilled greater trust among stakeholders by ensuring timely project completion, financial discipline, and comprehensive disclosures. These measures have not only improved market dynamics but also encouraged developers to adopt sustainable practices. The Act's emphasis on environmental clearances and adherence to sustainable construction norms has led to the increased use of green technologies and eco-friendly materials in real estate projects. The study presents case studies highlighting successful implementations of sustainable practices post- RERA enforcement. These cases illustrate how regulatory frameworks can drive the adoption of sustainability in construction and development processes. The analysis underscores the role of RERA in fostering a culture of compliance and ethical practices, which is crucial for sustainable urban development. Moreover, the paper explores the broader implications of RERA in promoting sustainability. It suggests that while RERA has made significant strides in reshaping the real estate sector, further enhancements are necessary to fully realize its potential in driving sustainable development. Policy recommendations include strengthening enforcement mechanisms, promoting awareness about sustainable practices among developers, and incentivizing green construction. In conclusion, RERA is not merely a regulatory measure but a catalyst for change, steering the real estate sector toward a more sustainable and responsible future. By promoting transparency and accountability, RERA is laying the groundwork for a paradigm shift in sustainable real estate development in India.